Acute Q Fever in Israel: Clinical and Demographic Data 2006–2016. (4th October 2017) - Reisfeld, Sharon; Mhamed, Shayma Hasadia; Stein, Michal; Chowers, Michal
Abstract: Background: The clinical spectrum of the acute disease varies in different locations around the world. Israel is endemic for Q fever, and our hospital is located in a hyper-endemic area. The aim of our study was to describe the clinical characteristic of acute Q fever in our area. Methods: A historical cohort, including adult patients with a serologic diagnosis of Q fever. Demographic, clinical, laboratory, and imaging data were collected and analyzed. Serologic definitions for an acute disease were IgM phase 2 ≥50 and/or IgG phase 2 ≥100, and chronic disease was defined as IgG phase 1≥800. Results: During 2006–2016, 3352 blood samples were sent for serology to the reference laboratory, 205 (6.1%) were positive for Q fever. We observed an increase in positive results from 1.3 to 3.7% in 2007–2011 to 3.9–7.3% during 2012–2015, and up to 41% in 2016. Full data was available for 153 patients. Ninety-nine patients (65%) were male, median age was 50 years, and half of the patients had no comorbidities. The patients presented with fever in 85% of the cases, a respiratory symptom in 58%, rash was present in 7%. Anemia was present in 46 patients (30%), but leukopenia and thrombocytopenia were less common (6 and 16%, respectively). Liver enzymes were elevated in 29 patients (19%), and 49 patients (32%) had pneumonia according to chest X-ray. Seventeen patients had risk factors for a chronic disease: three of those had chronic infection at presentation, four patients had an appropriate follow-up; one patient developed a chronic disease shortly after the acute infection. Three patients died from other severe medical conditions and seven patients were not followed up. Although only 46 patients (30%) were discharged with a diagnosis of either Q fever or unspecified rickettsial disease, 74 (48%) were treated with doxycycline. Conclusion: Most of our patients had an unspecified febrile illness, 81% of them had normal liver tests, as oppose to published data from Israel and Europe, where elevated liver enzymes were reported in the vast majority of patients. Although there is a high index of suspicion and the acute disease is diagnosed frequently, only four out of 11 high-risk patients had an appropriate follow-up. Education about the management of high-risk patients is warranted. Disclosures: All authors: No reported disclosures.